LEARNING THE CIRCULAR ECONOMY IN THE REPUBLIC OF FINLAND: EDUCATIONAL PROJECTS - Sysoiev , Oleksii (Continuing Professional Education: Theory and Practice, 2024)
The article discusses the role of education in achieving the goals of sustainable development, which is closely related to the transition to a circular economy, a new economic model aimed at minimizing the negative impact of civilizational activity of mankind on the environment. The use of educational projects in teaching the circular economy in the Republic of Finland, which is the European leader in the implementation of circular economic models, is analyzed. It is emphasised that in Finland, circular economy education is provided at all levels of education, starting with pre-school education, and continuing in general secondary, vocational, higher and adult education. It is emphasised that the circular economy is an inter-societal economic model that is needed in all sectors of the economy, and therefore it is necessary to teach the circular economy to all specialists of various profiles and specialties. It is shown that the organization of circular economy training is clearly reflected in the series of educational projects on the circular economy «Circular Economy for All Levels of Education», implemented in Finland with the support of the Sitra Foundation. Specific examples of educational projects on the circular economy for general secondary education institutions, colleges and universities are provided. The role of the teacher as a project leader and manager is important. Teachers use different strategies for evaluating projects, but traditional or multiple-choice exams are not used. Customers of educational products (projects) can be: a company from any sector of the economy, an association, a project organization, a municipality or a city, a community or an individual. The examples of these projects convincingly testify to their practical orientation.